Adaptation of the Multicultural Competence Perceptions Scale to the Culture of Kosovo (Architecture Image Studies, 2025)
This study aimed to adapt the Multicultural Competence Perceptions Scale to the cultural context of Kosovo. Conducted with a sample of 319 participants, the scale was translated into Albanian by expert translators, ensuring linguistic equivalence. Both the Turkish and Albanian versions were evaluated by teachers proficient in these languages, confirming the consistency of the items' meanings. The reliability analysis based on the four-factor structure of the scale showed that factor loadings were statistically significant (p < .001), with most values above 0.30, indicating adequate representation of the factors. Confirmatory Factor Analysis (CFA) results demonstrated good model fit indices, confirming the scale's four-factor structure. Some differences in factor structures across cultures were attributed to cultural and linguistic variations. While Kosovar culture shares some similarities with Turkish culture, the use of Turkish and Albanian as teaching languages contributed to the stability of the scale’s factor structure. The study emphasizes the importance of considering cultural and linguistic contexts in scale adaptation studies. It suggests that the scale can be effectively used in both pre-service and in-service teacher training in Kosovo. Enhancing multicultural competencies among educators is deemed essential for managing cultural diversity effectively. The scale also holds potential for use in broader academic and field research, contributing to diverse findings across various contexts.